PENGARUH MODAL SOSIAL TERHADAP PRODUKTIVITAS USAHATANI KOPI DI LMDH KARAMAT JAYA KECAMATAN CISURUPAN KABUPATEN GARUT - Vini Aisyah Aminingrum; Ahmad Choibar Tridakusumah (Universitas Galuh, 2022)
This study aims to analyze the effect of social capital on the productivity of coffee farmers at LMDH Karamat Jaya, Cisurupan District, Garut Regency. This research design uses quantitative research with survey methods, and uses Multiple Linear Regression analysis. Respondents of this study amounted to 63 samples with a population of 167 coffee farmers. The results showed that the majority of farmers in LMDH Karamat Jaya had low productivity with 48 farmers still below the average productivity of 993,8 kg/ha/year. The social capital owned by coffee farmers in LMDH Karamat Jaya is high in terms of trust, network, participation, social norms, and reciprocity. The very high dimension of social capital is the dimension of trust. The results of multiple linear analysis show that trust, participation, and social norms have a significant effect on the productivity of coffee farmers. The variables that have no effect on the productivity of coffee farmers are network and reciprocity.